One hundred years of Drosophila cancer research: no longer in solitude - Santiago Nahuel Villegas (The Company of Biologists, 2019)
When Mary Stark first described the presence of tumours in the fruit fly Drosophila melanogaster in 1918, would she ever have imagined that flies would become an invaluable organism for modelling and understanding oncogenesis? And if so, would she have expected it to take 100 years for this model to be fully accredited? This Special Article summarises the efforts and achievements of Drosophilists to establish the fly as a valid model in cancer research through different scientific periods.